Requirements for Using Interest Rates As An Operating Target for Monetary Policy : The Case of Tunisia - Durre, Alain (IMF Working Papers; Working Paper ;, 2009)
This paper discusses the use of interest rates as the operating target for monetary policy in Tunisia and the roadmap for establishing the other building blocks of an inflation targeting framework. It argues that strengthening the effectiveness of the current monetary policy framework will facilitate the adoption of inflation targeting over time.